Permohonan Penetapan Perkara Dispensasi Kawin Pada Pengadilan Agama Surabaya: (Studi Putusan: 2194/Pdt.P/2024/PA.Sby) - Ayu Mutiara Risky; Indah Purbasari (Referendum : Jurnal Hukum Perdata dan Pidana, 2024)
Marriage dispensation is a civil case, namely granting permission to prospective brides and grooms who wish to marry but are prevented by age requirements according to the provisions of Law Number 16 of 2019. Marriage is a sacred thing to form a family. The Religious Court is the place where marriage dispensation cases are filed. Compelling reasons with supporting evidence must accompany the case application. This article is using normative research, and the Statue Approach and Case Approach research types. This research aims to analyze the decision of the Surabaya religious court number 2194/Pdt.P/2024/PA.Sby. This article covers the chronology of the trial, Judge considerations, and factors that influence the judges to rejector grant request for the marriage dispensation.